Vibrational Spectroscopic Studies on the Td-type N,N’- dimethylethylenediamine(II)tetracyanometallate(II) Benzene Clathrates - Bayrak, Celal (Asian Journal of Chemistry, 2010)
FT-IR spectra of Mn(DMEDA)M(CN)4·C6H6 (M = Zn, Cd or Hg; DMEDA = N,N'- dimethylethylenediamine) and FT-IR and FT-Raman spectra of Cd(DMEDA)M(CN)4·C6H6 (M = Cd or Hg) are reported. All the vibrational modes of coordinated DMEDA are characterized. The spectral features suggest that these compounds are similar in structure to the Hofmann-Tdtype clathrates.